Mobile Health and Wellness Project: A binational collaboration of frontline health services to the Latino population in the United States in times of COVID-19 - Rosales, Cecilia B.; Dávila Chávez, Hilda; Flynn, Michael A.; Lara, Juanita; Lira Chávez, Isaura Angélica; Olivares Marín, Leonardo; Romero Rangel, Alejandra; Hirata Okamoto, Ricardo; Rangel Gómez, Maria Gudelia (Frontiers in Public Health, 2023)
Hardly reached communities in the United States greatly benefit from collective efforts and partnerships from Community Based Organizations, Health Institutions and Government Agencies, yet the effort to engage in this collaborative effort is minimal and funding to support these projects is lacking. The COVID-19 Pandemic exacerbated on a national scale what many vulnerable communities experience regularly; difficult access to basic medical care, information and support. In an effort to directly engage with community organizations and curb the infection rate of the COVID-19 virus within vulnerable communities, the US Centers for Disease Control and Prevention (CDC) launched its first targeted effort to partner directly with community based organizations. This article will highlight the first pilot year of activities and key results of COVID-19 education and vaccination efforts by the Mobile Health and Wellness project. This is a fleet of 11 Mobile Health Vehicles managed by the Mexico Section US-Mexico Border Health Commission in partnership with Alianza Americas, Latino Commission on AIDS, and the CDC, targeting Latino, Immigrant and rural communities across the US.